Management of Delayed Onset Postoperative Hemorrhage after Anastomotic Urethroplasty - L. A. Bertrand; S. P. Elliott; B. N. Breyer; B. A. Erickson (Case Reports in Urology)
Excision with primary anastomosis (EPA) urethroplasty is generally the preferred method for short strictures in the bulbar urethra, given its high success rate and low complication rate compared to other surgical interventions. Bleeding is a presumed risk factor for any surgical procedure but perioperative hemorrhage after an EPA requiring hospitalization and/or reintervention is unreported with no known consensus on the best course for management. Through our experience with three separate cases of significant postoperative urethral hemorrhage after EPA, we developed an algorithm for treatment beginning with conservative management and progressing through endoscopic and open techniques, as well as consideration of embolization by interventional radiology. All the three of these cases were managed successfully though they did require multiple interventions. We theorize that younger patients with more robust corpus spongiosum and more vigorous spontaneous erections, patients that have undergone fewer prior urethral procedures and therefore have more prominent vasculature, and those patients managed with a two-layer closure of the ventral urethra without ligation of the transected bulbar arteries are at a higher risk for this complication.